Urgensitas perencanaan strategis dan pengelolaan sumber daya manusia madrasah era revolusi industri 4.0 - Moch Charis Hidayat; Aldo Redho Syam (AL-ASASIYYA: Journal Of Basic Education, 2020)
Madrasah managers must manage the human resources of their institutions as a strategic step to make the task and link in a match to avoid mistakes strategic steps as effective, professional, and as prospective as possible. The urgency of human resource management is a very important aspect of the madrasah education process in general. This paper examines the study of the urgency of strategic planning and management of human resources in madrasah. This paper is the result of a literature review with data obtained from document study activities, both from reference books and international and national journals. This study proposes findings that the urgency of strategic planning and human resource management in the industrial revolution era 4.0 at the current madrasah is essential to avoid disaster or madrasa collapse, madrasa managers are expected to be able to manage their madrasah in accordance with the basic needs and management systems required by each stage of the cycle his life. One of the management functions that must be properly managed is strategic planning, which is planning that is able to predict the life, resilience, and progress of madrasah in the future by improving functions in the management of human resources must be carried out optimally, by focusing on achieving madrasah goals that have been set and implementing them on programs and activities, which then develop, including in terms of data collection to evaluate the effectiveness of the program.